Graham-Little-Piccardi-Lasseur Syndrome: Report of a Case - Martins Nóbrega, Monisa (2016)
Graham-Little-Piccardi-Lasseur Syndrome (SGLPL) is characterized by a progressive multifocal scarring alopecia of the scalp associated with disseminated follicular hyperkeratosis and non-scarring axillary and pubic hypotrichosis. These clinical aspects may occur simultaneously, although alopecia of the scalp often precedes the other findings in months to years. It affects mainly adult females and is considered a rare disease. Treatment is challenging with many suggested medications but with controversial results. We report the case of a female patient with an area of alopecia in the right parietal region, paravertebral violaceous pruritic polygonal papules, hyperchromic macules with white reticular lesions on the oral mucosa as well as a slight hypotrichosis of the axillae. A slight improvement was observed after oral hidroxizine associated with topical clobetasol propionate and intralesional betamethasone in the limits of the alopecic area.